Coping Strategies in the Spanish Population: The Role in Consequences of COVID-19 on Mental Health - Molero Jurado, María del Mar; Pérez-Fuentes, María del Carmen; Fernández-Martínez, Elena; Martos Martínez, África; Gázquez Linares, José Jesús (Frontiers in Psychiatry, 2021)
The worldwide health emergency caused by COVID-19 is a new challenge for humanity which individuals respond to in a diversity of ways. The type of coping people use in such a situation could lead to positive or negative consequences to their health. Our objective was to analyze the use of coping strategies in the general population with attention to sociodemographic variables, and to test the capacity of these strategies for mediating in repercussions on mental health. The 1160 adults who participated in this study answered the Cognitive Emotion Regulation Questionnaire (CERQ-S) and General Health Questionnaire (GHQ-28). The data were collected in a CAWI (Computer Aided Web Interviewing). The results suggest that the coping strategies they used the most differed depending on sociodemographic characteristics, such as age, sex and education. Furthermore, two mediation models were estimated for positive and negative coping strategies in the relationship between the presence of COVID-19 near them and mental health. The “negative” coping strategies were found to exert an indirect effect as mediators in the impact that COVID-19 positive cases near them had on their health. The consequences to mental health of the impact of coping with adverse situations should not be underestimated and it is important to design programs to educate the population in coping strategies that promote their health.